Modernitas Alat Pendidikan Dalam Perspektif Artificial Intelligence Fenomena Kemajuan Zaman Pendidik Abad 21 - Muthmainnah, Nabilatul; Rahmayanti, Vitha Azalia; Faizin, Moh. (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
The rapid development of technology, like today, really supports innovation in various sectors. In the education sector, technology is an important aspect of supporting the effectiveness of the learning process. There is currently a change in education due to the integration of artificial intelligence (AI) technology, which influences the learning process. This research aims to analyze existing literature regarding the use of AI in the learning process as a modern educational tool in the era of the Industrial Revolution 4.0. This research used qualitative research methods, where information sources were obtained from literature analysis, case studies, and related sources. This information is produced in the form of descriptions and narratives regarding a change in the modernity of educational tools caused by the progress of the educational era. Research results show that the use of AI in 21st-century education paves the way for more adaptive, interactive and comprehensive learning approaches.